FDG PET/CT in a Case of Bilateral Tuberculous Epididymo-orchitis. (September 2019) - Ran, Pengcheng; Liang, Xiang; Zhang, Yu; Sun, Pengtao; Dong, Aisheng
Abstract : Abstract: Isolated genital tuberculosis is rare. We present a case of bilateral tuberculous epididymo-orchitis showing high FDG uptake on FDG PET/CT. In addition, the patient had a prostatic FDG-avid lesion, consistent with tuberculous prostatitis. This case indicates tuberculous epididymo-orchitis, especially in tuberculosis-endemic regions, should be considered as a differential diagnosis in patients with hypermetabolic epididymal or testicular lesions, including benign and malignant tumors, bacterial epididymo-orchitis, abscess, idiopathic granulomatous orchitis, and sarcoidosis.